Metode Pengendalian Jadwal Pembangunan Pelabuhan dengan Kombinasi Barchart dan Network Planning Studi Kasus Proyek PT. DOK Warisan Pertama - Usmanul Hayadi Umar; Nur Dzuraida (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
A construction company engaged in the construction of ports and docks, namely PT. DOK Warisan Pertama in Batam is running a port project in Batam City. The number of work items carried out in a project requires a good project management to run it. This study aims to review the port project scheduling currently being implemented by PT. DOK Warisan Pertama with the Critical Path Method (CPM) method. The results of the research carried out indicated that the project was completed within 39 weeks. There are several critical paths in the CPM planning for this project. This indicates that the job does not have a free float to complete the job. Making a CPM in this project can be used as a reference and evaluation in carrying out project work.